THE HOLY NAMES OF ALLAH IN "KUTADGU BILIG" AND ISSUES OF THEIR TRANSLATION INTO ENGLISH LANGUAGE (Scientific journal of the Fergana State University, 2024)
The examination and comparison of ancient monuments hold a unique significance in the history of global translation studies. This article specifically focuses on the interpretation of divine names in the work "Qutadgu Bilig," a prominent contribution to worldwide Turkic studies, and meticulously analyzes their translation into English. Given that the source was authored during a period when Islam was firmly established in Central Asia, it becomes evident that religious motives, features, and terminology occupy a significant role within it. The names of Allah carry immense importance in Islam, and it is crucial to convey this significance accurately in English translations, maintaining consistency with the original language.